Analisis Penilaian Kinerja Keuangan Menggunakan Metode Economic Value Added (EVA) Dan Market Value Added (MVA) - Rama Danu Ikhsan; Paul Usmany; Hempry Putuhena (Jurnal Ilmiah Raflesia Akuntansi, 2025)
— Technology companies are one of the rapidly growing sectors and have great potential to be developed, especially in the current era of digitalization. This study aims to see how EVA and MVA-based performance measurements are in technology companies in 2020-2022. There are 2 measurement methods, namely the Economic Value Added (EVA) and Market Value Added (MVA) methods. The approach taken to answer the research objectives is a descriptive quantitative approach. This study uses 12 companies as samples and observations were carried out for 3 years, so the number of observation data is 36. Using the EVA and MVA methods, technology companies can find out whether the strategies and investments made have provided optimal results or not. The results of this study show that the EVA value is greater than 0. So that it can increase investor confidence in the company's performance and has the potential for future growth. From the MVA perspective, it shows that 10 companies have good financial performance because they have an MVA value of more than 0. But 1 company experienced fluctuations and 1 company had an MVA value of less than 0